Pengembangan Media Origami Mufrodat Berbasis Model Team Games Tournament (TGT) untuk Meningkatkan Motivasi Belajar Bahasa Arab Siswa Kelas VI MI Matholi’ul Falah Nambi - Syafira Nur Fitriani; Roihatul Lailiyah; Ririn Inayatul Mahfudloh; Nur Fatih Ahmad (JURNAL AL-IHDA' : Media Ilmiah Bahasa Arab, 2025)
The purpose of this study is to formulate Origami Mufrodat learning materials incorporating the Team Games Tournament (TGT) model to strengthen students' drive for Arabic language acquisition in grade VI at MI Matholi'ul Falah Nambi. This study utilized a Research and Development (R&D) methodology based on the ADDIE framework, which includes analysis, design, development, implementation, and evaluation phases. The data collection process utilized observation, questionnaires, interviews, and documentation. The evidence suggests that the formulated Origami Mufrodat media is valid, practical, and effective. The effectiveness analysis obtained 87%, labeled as very effective, whereas the feasibility testing through teachers' and students' feedback obtained 86%, labeled as very feasible. The integration of origami-based media with the TGT model successfully created an interactive, enjoyable, and collaborative learning environment that enhanced students’ intrinsic and extrinsic motivation. Therefore, Origami Mufrodat media incorporating the TGT model constitutes a fitting alternative learning approach for Arabic language pedagogy at the Madrasah Ibtidaiyah educational level.